2016
DOI: 10.1007/s00268-016-3620-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Perioperative Dexamethasone and Different NSAIDs on Anastomotic Leak Risk: A Propensity Score Analysis

Abstract: BackgroundPerioperative use of nonsteroidal anti-inflammatory drugs (NSAIDs) is associated with risk of anastomotic leak (AL). However, concomitant use of other drugs could infer a bias in risk assessment. Thus, we aimed to interrogate the risk of AL associated with NSAIDs and steroids used perioperatively.MethodsThis study includes a consecutive series of patients having surgery involving an intestinal anastomosis from Jan 2007 to Dec 2009. Data records included demographic, perioperative, and surgical charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Some authors recommend that the NSAIDs should be abandoned after primary colonic anastomosis because of the increase of leak rate that has been consistently demonstrated in experimental and clinical studies [35][36][37][38][39][40] . This find is due to an effect on collagen metabolism leading to weakened tissue around the anastomosis and on the risk of thrombosis formation leading to a decrease of anastomotic blood flow and ischemic damage.…”
mentioning
confidence: 99%
“…Some authors recommend that the NSAIDs should be abandoned after primary colonic anastomosis because of the increase of leak rate that has been consistently demonstrated in experimental and clinical studies [35][36][37][38][39][40] . This find is due to an effect on collagen metabolism leading to weakened tissue around the anastomosis and on the risk of thrombosis formation leading to a decrease of anastomotic blood flow and ischemic damage.…”
mentioning
confidence: 99%
“…Another factor that can be speculated upon is the low rate of patients with preoperative steroid use in our cohort. Although there is still some debate on the real impact of steroid use on AL risk and the definition of steroid use is variable, in previous prospective or retrospective studies, its rate in the pretreatment periods in colorectal surgeries ranged from 2.2 to 5.3% [42,43,44,45,46]. In this study, only four patients (0.7%) were classified as using steroids, although a lower rate of steroid use might be the specific characteristic of our patients.…”
Section: Discussionmentioning
confidence: 99%
“…26 Interestingly, NSAIDs were indeed linked to an increased occurrence of sepsis (OR, 1.47; 95% CI, 1.05-2.06; P¼0.03). 26 Likewise Rushfeldt and colleagues 29 found no association between the use of diclofenac and the risk of anastomotic leak. The authors demonstrated that the administration of vasopressor, blood transfusions and the presence of malignancy were independent risk factors.…”
Section: Perioperative Nsaids and Anastomostic Leaksmentioning
confidence: 99%
“…The authors demonstrated that the administration of vasopressor, blood transfusions and the presence of malignancy were independent risk factors. 29 In another large cohort study, patients enrolled in the Swedish Colorectal Cancer Registry were not at risk of anastomotic leak after the perioperative administration of NSAIDs for rectal cancer surgery. 28 In agreement with that investigation, Karlsson and colleagues 32 showed no association between the use of NSAIDs and anastomotic leaks after rectal cancer surgery.…”
Section: Perioperative Nsaids and Anastomostic Leaksmentioning
confidence: 99%